Modified WIC test: an efficient and effective tool for evaluating pipeline girth weldability. (19th May 2017) - Kurji, R.; Coniglio, N.; Griggs, J.; Ghomashchi, R.
ABSTRACT: The Welding Institute of Canada (WIC) test is a simple and standardised weldability test for hydrogen assisted cold cracking that was developed in the 80s. It has been extensively utilised by the industry to qualify safe welding envelopes but the difficult access to the weldment by instrumentation hinders its use for scientific research. Moreover the lack of repeatability arising from the traditional manual deposit and the short weld length causes industrial trials to have a low success rate. The present work proposes a modified geometry, referred to as the modified WIC (MWIC) test that shows: (1) an improved success rate of weld deposition, (2) an enhancement to instrument the weldment and (3) welding conditions in better accordance with the field pipeline girth welding conditions. The design is validated under a mechanised, shielded metal arc welding process with the cellulosic electrodes used for in-field pipeline construction.